Conservatism And Transfer Pricing On Tax Avoidance: Tax Shelter Approach - Bayu Pamungkas; Setu Setyawan (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of conservatism and transfer pricing on tax avoidance. This study uses a tax shield that has a positive impact on tax aggressiveness as a tool for tax defense that produces interest expenditures as a taxable income deduction to assess tax avoidance activities. Sample determination in this study using purposive sampling method. The sample in this study consisted of 579 observations from 193 non-financial service sector companies on the Indonesia Stock Exchange in the period 2016-2018. Panel data estimation with Stata statistical test version 15 was used as the analysis method. The results show that conservatism and transfer pricing are not used as arguments for lowering tax burdens, but as a way of fulfilling corporate tax obligations. This research is potentially relevant to academics, researchers, and regulators. By examining the factors of conservatism and transfer pricing against tax avoidance can be taken into consideration in future policy making by regulators in this case the Director General of Taxes on the actions of companies that take advantage of loopholes in tax laws to minimize the tax burden with maximum profits.